Optimization of the management system for mitigating the consequences of water area pollution during the crisis - Kotenko, S.V; Maslii, N.D; Kasianova, V.A; Bezpartochnyi, M.G; Nadtochii, I.I (Natsional'nyi Hirnychyi Universytet. Naukovyi Visnyk, 2021)
Purpose. The study is aimed at optimizing and reducing delays in crisis situations in the operation of decision support systems to eliminate the consequences of pollution of water areas. Methodology. The presented study uses the fundamental provisions of modern science to find the optimal solution in crisis situations. Methods of abstraction and mathematical formalization were used to solve the problem of minimizing the delay time of information packets in providing critical information in conditions of overloading information channels. Findings. It has been proven that a decrease in the volume of losses is possible in the case of effective management of the elimination of pollution, prompt minimization of its consequences. It has been established that the effectiveness of management to minimize the consequences of an accident is determined by the effectiveness of the information system, and largely depends not only on relevant information, but also on the timeliness of its receipt by the subject of decision-making. A mathematical model and an algorithm for optimizing information flows have been created, which provide minimal delays in obtaining information even under conditions of extreme load of the information system. It has been proven that the task of effective management of an information system can be reduced to minimizing the delay in the provision of critical information. As a result of the study, it was found that for a large information system, which includes more than forty subunits and satellite systems, the use of the proposed approach provides a decrease in the response delay to an information request of time, which does not exceed a minute. Originality. To prevent delays in the operation of the information management system for the elimination of pollution of water areas, a scientific and applied approach to optimize the information system is proposed, which uses the theory of graphs and Ant Colony Optimization Algorithm and implements effective management of information flow. A mathematical model and an original algorithm have been developed that allow reducing delays in work and providing a resource utilization factor better than the existing analogues. Practical value. The presented approach will make it possible to increase the efficiency and reliability of information systems for managing technogenic pressure on water areas in crisis situations, reduce the time for providing the necessary information and, thereby, reduce the consequences of pollution and the costs associated with their neutralization. The data obtained in the course of the study are approximated by a polynomial equation, making it possible to evaluate the effectiveness of using the proposed method depending on the number of nodes of the information system and the requirements for limiting the delay time of information.